Guía para la intervención de espacio publico en ciudades consolidadas (2021)
An exploration about the state of the public space in Latin-American and Bogotá was carried out, according to the results obtained we can establish that the conditions are not optimal, because the relationship between the upper social class with having more public space and the working and lower class being left out and even sometimes the Outskirts of the city, it also has been noticed that in some public spaces people don’t like to appropriate of this places and the particular reason for that is because they perceive it as insecure and the lack of use makes them to deteriorate constantly.